2021
DOI: 10.1159/000518722
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of miR-126 and miR-122 Expression and Response of Imatinib Treatment on Its Expression in Chronic Myeloid Leukemia Patients

Abstract: <b><i>Background:</i></b> MicroRNAs (miRNAs) have been observed to exhibit altered expression patterns in chronic myeloid leukemia (CML). Therefore, this study was aimed to evaluate the clinical importance of miR-126 and miR-122 expression in concert to imatinib response in CML patients. <b><i>Methods:</i></b> The present study included 100 CML and 100 healthy subjects. The expression of the 2 miRNAs was performed using TaqMan probe chemistry, and snU6 was used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Referring to Table , it is evident that 16 out of the top 20 ncRNAs associated with Imatinib have been validated through the PubMed-referenced literature. For example, after treatment with Imatinib in chronic myeloid leukemia (CML) patients, a significant increase in the expression of miR-126 was observed . Furthermore, a comprehensive analysis of oncogenic and tumor suppressor miRNA expression profiles in CML patients highlighted substantial upregulation of miR-21 in Imatinib-resistant patients compared to responsive counterparts …”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Referring to Table , it is evident that 16 out of the top 20 ncRNAs associated with Imatinib have been validated through the PubMed-referenced literature. For example, after treatment with Imatinib in chronic myeloid leukemia (CML) patients, a significant increase in the expression of miR-126 was observed . Furthermore, a comprehensive analysis of oncogenic and tumor suppressor miRNA expression profiles in CML patients highlighted substantial upregulation of miR-21 in Imatinib-resistant patients compared to responsive counterparts …”
Section: Experiments and Resultsmentioning
confidence: 99%
“…In patients with higher miR-363 expression in PB samples, early allogeneic transplantation (allo-HSCT) was recommended as a more effective strategy compared to chemotherapy but improved OS was found in those with a low level of miR-363 [110]. Several adult CML studies identified a single or set of specific miRNAs, which could be useful for the prediction of imatinib response [120,121,123,125]. In MM patients, the aberrant expression of other miRNA was found mostly in association with shorter PFS and OS [95,127,[129][130][131][133][134][135]137] and bortezomib response [94,127].…”
Section: Aberrant Microrna Expressions In Diagnosis Prognosis and Mon...mentioning
confidence: 99%
“…Obinutuzumab-induced CD16 stimulation and bortezomib led to an up-regulation of miR-155-5p and miR-29b in follicular lymphoma and in murine models of cutaneous T-cell lymphoma, respectively [ 184 , 185 ]. In CML, dasatinib affected the expression of miR-let-7d, miR-let-7e, miR-15a, miR-16, miR-21, miR-130a and miR-142-3p, while imitanib was shown to modulate miR-15a, miR-21, miR-122, miR-126, and miR-130a levels [ 186 , 187 , 188 ].…”
Section: Clinical Applications Of Mirnas Focusing On Hematological Ma...mentioning
confidence: 99%